Baby walker related injuries--a continuing problem. Issue 1 (March 1991) - Coats, T J; Allen, M
Abstract : Baby walkers have been associated with burns, head trauma and other types of injury. A retrospective study of all infants under the age of two years attending an accident and emergency unit demonstrated 22 injuries associated with baby walkers from a total of 1049 attendances. The most serious injuries were three skull fractures, with the most common mechanism being of a fall downstairs in the walker. Injury while in a baby walker occurred with a similar frequency to injury due to road traffic accidents. We conclude that despite previous warnings Baby Walkers still represent a considerable hazard to infants.